GAMBARAN KARAKTERISTIK SAFETY LEADERSHIP PT. RND DI JAKARTA-SURABAYA TAHUN 2012 - Utami, Desyawati (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2017)
This reseach will describe and explain the overall the characteristics of safety leadership in PT. RND, Jakarta-Surabaya in 2012 with in-depth interviews and direct observation for the leaders in PT. RND conducted in April-June 2012. Implementation of safety given by the supervisor 3, although the decision-making for implementation of safety continue through the director. Disengagement supervisor and team leader of safety programs in the field resulted in the implementation of safety systems are not effective in PT. RND. The leaders in PT. RND do not have the perspective of safety which is reflected in their personality, leadership style and best practices in leading employees to implement safety effectively. The results of this research obtained personality, which is owned by the leaders of PT. RND is still not optimal on the characteristics of emotional resilience. Transformational leadership style has been used by some leaders of PT. RND in leading employees but not yet used by directors and supervisors 3. Best practices characteristic held by the leaders of PT. RND are not optimal in the vision and communication. Characteristic of safety leadership in PT. RND is not optimal as an unstable emotional resilience. The leaders in PT. RND does not have a clear plan in the execution of the work, the difference in the vision and the communication path that overlaps giving an obstacle to the leaders of PT. RND in leading the workers.